Source reduction: Towards improving waste management strategy and sustainability in Malaysia construction industry - Osman, Wan Nadzri; Mohd Nawi, Mohd Nasrun (Medwell Journal, 2016)
Construction industry involvement is very important in order to achieve environmental sustainability through the improvement of its waste management practices. In most of the countries especially developed countries, construction industry is the major user of energy and natural resources.Thus, issues such as excessive, depletion and degradation of natural resources and waste management has become more apparent among the public and private sector. Construction industry could be considered as one of the mega contributor to the environmental issues.This study will focus on the management of construction waste in Malaysia as an important issue to be discussed in the country.This is due to the construction waste management in Malaysia is at an unsatisfactory level.In this study, concept of sustainability, construction waste, waste management and source reduction has been thoroughly discussed and highlighted.